One‐Pot Synthesis of 6‐Aminopyrido[2, 3‐d]pyrimidin‐7‐ones. Issue 46 (25th November 2018) - Zinchenko, Anna M.; Muzychka, Lyubov V.; Kucher, Olexandr V.; Sadkova, Iryna V.; Mykhailiuk, Pavel K.; Smolii, Oleg B.
Abstract : One‐pot synthesis of 6‐aminopyrido[2, 3‐ d ]pyrimidin‐7‐ones from 4‐aminopyrimidine‐5‐carbaldehydes and the in situ N ‐protected methyl glycinate is developed. The obtained compounds have a polyfunctional character and provide opportunities for their use in drug design projects. Abstract : One‐pot synthesis of 6‐aminopyrido[2, 3‐ d ]pyrimidin‐7‐ones from 4‐aminopyrimidine‐5‐carbaldehydes and the in situ N ‐protected methyl glycinate is developed. The obtained compounds have a polyfunctional character and provide opportunities for use in drug design.